Spectroscopic properties of Tm3+ doped fluoroindate glass - Jerez, Vladimir A.; Araújo, Cid B. de; Messaddeq, Younes [UNESP] (SPIE, the international society for optics and photonics, 2003)
Optical absorption and fluorescence were investigated in Tm3+ doped fluoroindate glass. The spectroscopic parameters for transitions in the 4f11 configuration were determined. The fluorescence study revealed the origin of the frequency upconversion process as well as allowed to quantify the interaction between Tm3+ ions.
Keywords: Absorption spectroscopy; Attenuation; Doping (additives); Emission spectroscopy; Energy transfer; Fluorescence; Light absorption; Moisture; Photomultipliers; Photons; Tantalum; Absorption spectra; Excitation spectrum; Frequency upconversion emissions; Multiphoton relaxation; Glass